Efficacy of Endophytic Bacteria as Entomopathogens against Spodoptera frugiperda (Lepidotera: Noctuidae) on Corn (Zea mays L.) - Kurniawati Kurniawati; Arika Purnawati; Wiwin Windriyanti (The University of Lampung, 2025)
The fall armyworm (Spodoptera frugiperda) poses a problem for corn plants (Zea mays L.). The use of endophytic bacteria Bacillus sp. as an entomopathogen is expected to control the S. frugiperda pest. This study aims to determine the effective concentration of the bacteria and the active compounds produced by Bacillus sp. strain Bth 22 in controlling S. frugiperda. The research was conducted from August to October 2024 at the Plant Health Laboratory of the Faculty of Agriculture, UPN